2021
DOI: 10.54783/ijsoc.v3i4.406
|View full text |Cite
|
Sign up to set email alerts
|

MSMEs Marketing Strategy with the Use of Social-Media in the COVID-19 Pandemic Era

Abstract: Micro, Small, and Medium Enterprises, commonly abbreviated as MSMEs, is one of the pillars of the economy in Indonesia. It is proven that the MSMEs sector has repeatedly survived various crises that hit Indonesia starting from the monetary crisis in 1998 and the global crisis in 2008. Entering 2020, the world is again experiencing a more severe crisis, namely the COVID-19 pandemic. This crisis is seen as more severe because it has caused a worldwide health emergency that impacts other sectors, especially the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…Confidence in buyers represents a vital task in a business transaction connecting buyers and merchants. The absence of direct human contact is a drawback of online buying (Nurjaman, 2021). Previous research on the significance of trust in online business has revealed that consumers' confidence in information will positively improve the purchase transaction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Confidence in buyers represents a vital task in a business transaction connecting buyers and merchants. The absence of direct human contact is a drawback of online buying (Nurjaman, 2021). Previous research on the significance of trust in online business has revealed that consumers' confidence in information will positively improve the purchase transaction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In general, MSMEs use social media reach a broader market digitally, increase sales turnover, and provide a platform for branding and establishing communication with consumers (Putra et al, 2020;Gaffar et al, 2021;Kingsnorth, 2016;Utomo et al, 2019). Yet, during the COVID pandemic the urgency of MSMEs using social media in Indonesia has been based on the following reasons: a) consumers are active on social media; b) the easy contact with consumers; c) to increase band visibility; d) by acting as the widest WoM container; e) the need to have many types of platforms with different types of consumers; f) assisting in the targeting and retargeting of consumers; g) the need to use media more effectively; and h) to increase sales (Nurjaman, 2021).…”
Section: The Utilisation Of Digital Media: Social Mediamentioning
confidence: 99%
“…As promotional media, social media function to scale up the MSMEs. By using social media, MSMEs are helped to expand the network among consumers and also to increase product sales (Nurjaman, 2021).…”
Section: The Utilisation Of Digital Media: Social Mediamentioning
confidence: 99%
“…Since the advancement of technology in the 21 st century and during the fourth Industrial Revolution, people can readily acquire and access data or information through various mediums. According to Nurjaman and Hertanto (2022), it could be information about education, politics, culture, social and health issues, especially COVID-19, which are still highly debated presently. Sorakin et al (2022) stated that the COVID-19 pandemic had been fought against for almost two years.…”
Section: Introductionmentioning
confidence: 99%